Modelling crop-livestock systems for achieving food security and increasing production efficiencies in the Ethiopian highlands - Amede, Tilahun; Delve, Robert J. (Cambridge University Press, 2008)
An action research process was conductedwith communities in Gununo, southern Ethiopia (2000–2003), to develop alternative cropping strategies for achieving their food security and cash needs. Farmers identified three major production objectives depending on their household priorities and socio-economic status. In Group I, farmers are currently food insecure and want to produce enough food from their own farms. In Group II, they produce enough food but want to fulfil their financial needs. In Group III, farmers rely on off-farm activities and want to increase cash income. The current system mostly fulfils the nutritional requirement of Group II. Groups I and III were highly food deficit from their own farms, with production covering less than seven months per year and fulfilling <50% of the recommended daily allowances (RDA) for human nutrition. Using a linear programming optimization model, it was possible to fulfil the RDA of Group I by reallocating the cropping area of maize, sweet potato, coffee and wheat to potato, enset and kale in proportions of 50, 29 and 15%, respectively. To satisfy both financial and nutritional needs of Group II, an increase in the proportion of coffee and beans by about 29 and 7.3%, respectively, over the current land allocation was needed. This shift would triple their cash income. The cash income of Group III increased four-fold by full replacement of the cereals and root crops by coffee (48%) and teff (52%), though the total income was not enough to secure food security due to their small landholdings. In farms of Groups I and II, the shift to the suggested cropping will reduce soil erosion by about 40%, while it will have no effect on farms of Group III. This shift will reduce the quantity and quality of livestock feed, except for Group I. Moreover, it will increase the farm crop water requirement 17.5 and 37% in Groups I and III (resource poor households) and reduce it in resource rich households of Group II. These changes did not imply extra labour in any groups. Whilst this model can optimize systems for food security and cash income, its research for development value is in identifying possible intensification strategies for farming systems and their implications on the farming systems, rather than generating practical recommendations for all cropping systems.